Role of Female Participation in the Changing Economy of Sunderban Blocks of South 24 Parganas, West Bengal, India (International Journal of Scientific Research and Management (IJSRM), 2015)
Sunderban is the largest space of tidal halophytic mangrove forest in the globe. It is a delta of the rivers Ganga, Brahmaputra and Meghna and located in West Bengal state of India and neighboring country of Bangladesh. The present paper deals with the changing nature of work participation with the changing agroclimatic condition in Sunderban blocks of South 24 Parganas and its effect on the traditional economy of that region. Economy is such an indicator which determines the status of living. The present paper looks into the recent changes occur in the composition of workforce of that region. Thus the paper will also give emphasis on the relation between the climate change and its impact on regional economy. Not only but also the paper will try to evaluate the role of female participation in changing economy of Sunderban blocks of South 24 Parganas as a part of adaptation to maintain the livelihood.